Kesadaran Pendidikan Orang Tua Pemulung dalam Mendukung Motivasi Belajar Anak di Sekolah Islam Impian - Febriansa Febriansa (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze the educational awareness of scavenger parents in supporting their children’s learning motivation at Sekolah Islam Impian, a free school for children from marginalized families. This research employed a qualitative approach with a case study method. The participants included the principal, teachers, scavenger parents, and students selected through purposive sampling. Data were collected through interviews, observations, and documentation and analyzed using the Miles, Huberman, and Saldaña model. The findings indicate that scavenger parents have a strong awareness of the importance of education as a means of improving their children’s future quality of life. This awareness is reflected in the provision of motivation, attention, and support for children’s learning activities. Despite economic limitations, parents continue to encourage their children to attend school and pursue their aspirations. Furthermore, Sekolah Islam Impian plays an important role in strengthening parents’ educational awareness through continuous communication and guidance. The study concludes that parental educational awareness and the synergy between families and schools contribute significantly to enhancing the learning motivation of children from marginalized backgrounds.